Papaverine increases human serum albumin glycation - Ahmadzadeh, Alireza (Springer Netherlands, 2014)
Glycation is a non-enzymatic reaction that is initiated by the primary addition of sugars to amino groups of proteins. In the early phase of glycation, the synthesis of intermediates leads to formation of Amadori compounds. In the last phase, advanced glycation end products (AGE) are irreversibly formed following a complex cascade of reactions. It has recently been shown that glycation also affects diabetes-related complications and Alzheimer’s disease. In this study, human serum albumin at a concentration of 10 mg/ml was incubated in PBS with 40 mM of glucose and in different concentrations of papaverine (25, 100, 250, 500 μM) for 42 days at 37 °C. HSA with no additives as well as with glucose 40 mM were incubated as a control and as a glycated sample, respectively. Following the incubation, the samples were prepared for circular dichroism, fluorescence and absorbance techniques. The results showed that in presence of papaverine and glucose, the glycation of HSA increased notably compared with the glycated sample. In conclusion, in this work, we showed that papaverine affects HSA and increases its glycation level.